Performance Analysis of a Modified SC-FDMA-DSCDMA Technique for 4G Wireless Communication. (24th November 2014) - Kedia, Deepak; Modi, Arti
Abstract : Single-carrier FDMA (SC-FDMA) is becoming more and more popular in multiuser communication because of its lower PAPR value. Apart from this, many other hybrid access techniques have also been explored in the literature for application to 4G wireless mobile communication. Still there is a need to explore newer techniques which could further reduce the PAPR value without any degradation in system BER. Keeping this in view, a modified hybrid technique SC-FDMA-DSCDMA has been proposed in this paper and it is found to provide significantly lower PAPR than SC-FDMA system with no degradation in BER performance. This paper extensively compares the BER and PAPR performance of various other multicarrier techniques for 4G wireless communications such as OFDMA, MC-DS-CDMA, and SC-FDMA with proposed SC-FDMA-DSCDMA scheme. Simulation results show that SC-FDMA-DSCDMA technique performs better than any other OFDM-CDMA based system for wireless communication.